CONVERSION CHEMOTHERAPY WITH A MODIFIED FLOX REGIMEN FOR BORDERLINE OR UNRESECTABLE LIVER METASTASES FROM COLORECTAL CANCER - Kamishov, S.V.; Tillyashaikhov, M.N.; Islamov, Kh.D.; Bresaler, R.S.; Niyozova, Sh.Kh. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
metastasectomy for fluorouracil, leucovorin, and oxaliplatin (mFLOX (mFLOX)) (mFLOX (mFLOX) In patients with CRC-derived liver metastases receiving conversion chemotherapy with a regimen Evaluation of treatment outcomes of PG / NEOP liver metastases. Materials and methods: hepatic metastasis one-centered retrospective analysis of patients. PG / NEOP from CRC treated with mFLOX chemotherapy (mFLOX): with surgery: B / U disease was diagnosed with at least one: more than four injuries, liver damage arteries or the involvement of portal vein or bile structures. Results: PG / NEOP meets the criteria for liver metastases 35% of the 54 consecutive patients were evaluated. More than four liver injuries in 35% of patients, 16 (29%) - primary vascular damage. structures, 16 (29%) - bile ducts. Surgery in all patients after chemotherapy operation was performed, 42 (77%) R0 resections were performed. 37.2 months after median follow-up, from median disease survival (PFS) was 16.9 months and median total survival (OS) was 68.3 months. With resection R0 in comparison, R1-R2 resections were associated with PFS and OS (PFS: risk level 2.65; P = 0.007; OS: risk factor 2.90; P = 0.014). Conclusion: PG / NEOP in the liver from CRC using conversion chemotherapy using mFLOX mode (mFLOX) treatment of metastases, high frequency of R0 resection, and positive survival outcomes. mFLOX (mFLOX) is a cheaper option for conversion chemotherapy, among other proposed options.